2022
DOI: 10.1111/jam.15645
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens NK4 siderophore promotes plant growth and biocontrol in cucumber

Abstract: Aims:To test the effect of zinc oxide nanoparticle (ZnO-NP) supplementation for enhancing the efficacy of Pseudomonas fluorescens NK4 siderophore as a biocontrol agent against P. viridiflava NK2 and a plant growth promoter.Methods and Results: Cucumber seedlings were treated with a suspension of P. fluorescens NK4 and its siderophore generated in siderophore-inducing medium (SIM), SIM supplemented with ZnO-NP (<100 nm) and SIM supplemented with Zn 2+ ions from Zn(NO 3 ) 2 . Supplementing SIM with ZnO-NP increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The Arachis hypogaea pot experiment was also conducted to evaluate the siderophore-producing LNPF1 isolate’s bioinoculant efficacy on plant growth and other physico-chemical parameters. Previous studies have shown that siderophores during the germination and emergence phases [ 47 ] increase the germination rate and seedling activity of popular crops such as tomatoes [ 48 ], cucumbers [ 49 ], and wheat [ 50 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…The Arachis hypogaea pot experiment was also conducted to evaluate the siderophore-producing LNPF1 isolate’s bioinoculant efficacy on plant growth and other physico-chemical parameters. Previous studies have shown that siderophores during the germination and emergence phases [ 47 ] increase the germination rate and seedling activity of popular crops such as tomatoes [ 48 ], cucumbers [ 49 ], and wheat [ 50 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that many plant-beneficial bacteria, as biocontrol agents, possess the T6SS (Marchi et al 2013 ), and most of these beneficial plant bacteria belong to the genus Pseudomonas. These bacteria can inhibit plant diseases and are considered an important source of biocontrol agents (Abo-Elyousr et al 2021 ; Al-Karablieh et al 2022 ; Gu et al 2022 ).…”
Section: T6ss Confers Resistance To Biotic Stressesmentioning
confidence: 99%
“…These microorganisms have been extensively studied for their application in biocontrol [90]. Multiple fluorescent Pseudomonas species utilize this mechanism in biocontrol applications [91][92][93]. However, several studies have reported the direct antimicrobial action of siderophores toward bacteria and fungi [90][91][92][93], suggesting their activity in antibiosis, not competition "sensu stricto".…”
Section: Competition For Ironmentioning
confidence: 99%
“…Multiple fluorescent Pseudomonas species utilize this mechanism in biocontrol applications [91][92][93]. However, several studies have reported the direct antimicrobial action of siderophores toward bacteria and fungi [90][91][92][93], suggesting their activity in antibiosis, not competition "sensu stricto". For example, Pseudomonas donghuensis produces two alternative iron chelators, pyoverdine and 7-hydroxytropolon [94].…”
Section: Competition For Ironmentioning
confidence: 99%